2021
DOI: 10.1017/ice.2021.44
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of antibiotic stewardship metrics for outpatient respiratory tract diagnoses and association of provider characteristics with inappropriate prescribing

Abstract: Objective: To determine metrics and provider characteristics associated with inappropriate antibiotic prescribing for respiratory tract diagnoses (RTDs). Design: Retrospective cohort study. Setting: Primary care practices in a university health system. Participants: Patients seen by an attending physician or advanced practice provider (APP) at their primary care office visit with International Classification of Disease, Tenth Revision, Clinical Modific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Most data come from the outpatient setting and describe the relative appropriateness of antibiotics for treating upper respiratory tract infections. Two studies in adult populations at major East Coast centers showed that APPs prescribed antibiotics at a rate about 15% higher than their physician colleagues [ 10 , 11 ]. In contrast, a study of pediatric patients based on Kentucky Medicaid data showed that physicians were 25% more likely than their nurse practitioner colleagues to prescribe an antibiotic for upper respiratory tract infection diagnoses [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most data come from the outpatient setting and describe the relative appropriateness of antibiotics for treating upper respiratory tract infections. Two studies in adult populations at major East Coast centers showed that APPs prescribed antibiotics at a rate about 15% higher than their physician colleagues [ 10 , 11 ]. In contrast, a study of pediatric patients based on Kentucky Medicaid data showed that physicians were 25% more likely than their nurse practitioner colleagues to prescribe an antibiotic for upper respiratory tract infection diagnoses [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, one survey reported that when compared with physicians, APPs were less likely to (1) report feeling that their training in antimicrobial prescribing was adequate, (2) feel that antibiotics were overused, and (3) correctly choose empiric therapy based on an antibiogram [ 9 ]. Additionally, outpatient data suggest a difference in appropriateness of antibiotic prescribing based on provider type, though such comparisons are not available from inpatient settings [ 10 , 11 ]. Understanding the composition of decision makers that hospital-based antimicrobial stewardship programs and ID consultants aim to support has significant implications for antimicrobial stewardship program strategy, development, and implementation.…”
mentioning
confidence: 99%
“…To determine the appropriateness of an antibiotic prescription, we adapted a tiered appropriateness assessment strategy, originally outlined by Fleming-Dutra et al [ 8 ] and validated in the UPHS PC practices by Degnan et al 9 ]. In this approach, encounters were assigned to 1 of 3 tiers based on how frequently antibiotic therapy would be justified for a particular diagnosis, as assessed by ICD-10-CM codes assigned at the encounter.…”
Section: Methodsmentioning
confidence: 99%
“…Excessive antibiotic use carries increased financial costs to patients, side effects including Clostridioides difficile infection, and risks of subsequent infections with drug-resistant organisms [ 6 , 7 ]. Respiratory tract diagnoses (RTDs) represent a significant portion of outpatient antibiotic prescribing, particularly in primary care, and antibiotic prescribing for RTDs is frequently unnecessary [ 8 , 9 ]. While outpatient stewardship interventions have been associated with decreased rates of antibiotic prescribing for RTDs, there is limited evidence on the long-term post-completion effects of such interventions [ 3 , 10–14 ], which has implications for the generalizability and maintenance of outpatient stewardship programs.…”
mentioning
confidence: 99%
“… 4 12 At least some of the increased prescribing for RTDs in the winter months is likely inappropriate. 11 Because these increases in antibiotic prescribing may drive antibiotic resistance, further understanding of seasonal prescribing patterns is vital to antibiotic stewardship efforts broadly. 5 …”
Section: Introductionmentioning
confidence: 99%